The Economic Effect of Chronic Comorbidities in Carpal Tunnel Syndrome Workers' Compensation Claimants, Washington State. Issue 12 (December 2018) - Marcum, Jennifer L.; McHugh, Anne; Foley, Michael; Adams, Darrin; Bonauto, David
Abstract : Objective: Assess the effect of chronic comorbidities on hours and earnings recovery following a carpal tunnel syndrome (CTS) claim. Methods: The hours and earnings profiles of Washington State workers' compensation claimants with CTS and controls, upper extremity fractures (UEF) claimants, were collected by linking to unemployment insurance data during 2007 to 2014. Chronic comorbidity status was determined from workers' compensation bills. Results: More (43%) CTS claimants had diagnosed chronic comorbidities than UEF (24%). CTS claimants and claimants with multiple chronic comorbidities had significantly higher odds of not working post injury and poorer hours and earnings recovery compared with UEF claimants and those with no chronic comorbidities. Conclusions: This research suggests that chronic conditions should be considered as barriers to return to work among injured workers. Abstract : Supplemental Digital Content is available in the text